An approximation to the planar harmonic impedance for interface waves in piezoelectric body - Eugeniusz J. DANICKI (Archives of Acoustics, 2009)
TIt is well known that spatial-temporal Green function characterizes sufficiently the elastic media. For the case of elastic interface waves which propagate at the interface between two, perfectly mechanically contacting piezoelectric half-spaces, this function, or its scalar counterpart that is the planar harmonic impedance, provides full characterization of electric properties observed at the interface, which can be applied in analysis of interdigital transducers embedded there, for instance. This impedance however is not easy for evaluation as a function of complex wave-number in the most interesting domain near the cut-off wave-number of bulk waves. Here, a perturbation analysis is presented exploiting the Stroh matrix formulation for piezoelectrics which yields the analytical approximation to the investigated electric impedance at the crystal planar cross-section.